Initial Electric Field Changes Of Lightning Flashes In Tropical Thunderstorms - Mohammad Sabri, Muhammad Haziq (2019)
Lightning has been observed to be initiated by a series of electric field (E-field) bipolar pulses known as Initial Breakdown (IB) pulses. However, the main problem with this observation is how the first pulse of IB is initiated when the existing background electric field inside thundercloud is not enough to initiate the emission of the first pulse of IB. Recent study in 2017 based on Florida thunderstorms found Initial E-field Change (IEC) process initiated the first pulse of IB. The IEC is a slowly varying field represents the temporal change in cloud conductivity. So far, there are no other published results regarding IECs from other parts of the world. Therefore, this thesis is motivated to provide independent validation results based on tropical storms to the observations and analysis of IECs in Florida. The aims to design and develop measurement system to measure the IECs and VHF emissions from lightning flashes by using Fast E-field, Slow E-field and VHF E-field sensors. Then, the temporal characteristics of VHF emissions and IECs initiated the first IB pulse are analyzed. The key finding is that all the examined first classic IB pulses in 80 tropical flashes within the reversal distance were found to be initiated by an IECs. From this analysis, it is found that the durations of IECs are longer and the magnitude of E-change are smaller for both Negative Cloud-to-Ground (–CG) and Intra-cloud (IC) flashes in tropical storms. It shows that, the IEC process of lightning flashes in tropical regions took longer to increase the local electric field in order to produce the first IB pulse because of the smaller magnitude of E-change. Besides, in Florida storms, the IEC process took a shorter time to increase the local electric field to produce the first IB pulse because of the larger magnitude of E-change. It is found that the VHF pulses for tropical thunderstorms started earlier before the onset of the IECs between 12.69 and 251.60 µs for the two normal IC flashes. Additional results show that, the VHF pulses for three IC flashes initiated by Positive Narrow Bipolar Events (+NBEs) were also detected before the onset of the IEC. The IEC started immediately after the detection of the +NBE and it is initiated by VHF pulses.